2015
DOI: 10.1093/ijnp/pyv045
|View full text |Cite
|
Sign up to set email alerts
|

Brain Histamine Is Crucial for Selective Serotonin Reuptake Inhibitors‘ Behavioral and Neurochemical Effects

Abstract: Backgound:The neurobiological changes underlying depression resistant to treatments remain poorly understood, and failure to respond to selective serotonin reuptake inhibitors may result from abnormalities of neurotransmitter systems that excite serotonergic neurons, such as histamine.Methods:Using behavioral (tail suspension test) and neurochemical (in vivo microdialysis, Western-blot analysis) approaches, here we report that antidepressant responses to selective serotonin reuptake inhibitors (citalopram or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
3
26
0
Order By: Relevance
“…We suggest that increased levels of pCREB are required for the retrieval of IA-LTM through activation of H 1 receptors. Consistently, earlier reports indicate that histamine signaling is necessary to trigger CREB phosphorylation in the hippocampus (17,57). The hippocampus is involved in both the aversive component of the IA and its contextual aspect as reviewed in the work by Izquierdo et al (58).…”
Section: Discussionsupporting
confidence: 66%
“…We suggest that increased levels of pCREB are required for the retrieval of IA-LTM through activation of H 1 receptors. Consistently, earlier reports indicate that histamine signaling is necessary to trigger CREB phosphorylation in the hippocampus (17,57). The hippocampus is involved in both the aversive component of the IA and its contextual aspect as reviewed in the work by Izquierdo et al (58).…”
Section: Discussionsupporting
confidence: 66%
“…The densitometric quantification was performed using a chemiluminescent photo finder (Carestream, model GL2200; Kodak, Rochester, NY, USA). pCREB densities were divided by their respective CREB densities within each sample to obtain pCREB:CREB ratio values …”
Section: Methodsmentioning
confidence: 99%
“…We recently showed that i.c.v. infusion of a-FMHis (5 µg/µL) M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 8 quickly and fully suppressed the release of brain histamine measured by microdialysis in mice (Munari et al, 2015) as well as in rats. CD-1 mice receiving equivalent injections of saline (i.c.v.…”
Section: Abt-239 Administration Transforms a Short-term Learning Evenmentioning
confidence: 96%